Natural Frequencies of a Cantilever Timoshenko Beam With a Tip Mass - Auciello, N.M (Engineering Transactions, 1995)
The aim of the present paper is to deduce the free vibration frequencies of cantilever structures with a tip mass at the free end, by taking into account the rotary inertia and the shear deformation. The analysis is conducted by dividing the beam into rigid bars with elastic constraints, extending a previous work by DE ROSA and FRANCIOSI[1]. The proposed method allows us to analyze beams with arbitrarily varying cross-sections, and numerical comparisons with some previous results found in the literature show the good performances of the approach.